11β-Hydroxylase (CYP11B1) gene variants and new-onset depression in later life - Ancelin, Marie-Laure (J Psychiatry Neurosci, 2021)
BACKGROUND: Cumulative exposure to high glucocorticoid levels is detrimental for the brain and may have particular implications in later life. A feature of late-life depression is increased cortisol secretion. Variants in the CYP11B1 gene, which codes for the enzyme responsible for cortisol synthesis, could influence risk of late-life depression, but this hypothesis has not been examined. We investigated the associations between variants in the CYP11B1 gene and late-life depression, taking into account history of depression and potential sex-specific effects. METHODS: We assessed depression in 1007 community-dwellers aged 65 years or older (60% women) at baseline and over a 14-year follow-up. A clinical level of depression was defined as a score of ≥ 16 on the Centre for Epidemiology Studies Depression scale or a diagnosis of current major depression based on the Mini-International Neuropsychiatric Interview and according to the criteria of the Diagnostic and Statistical Manual of Mental Disorders, 4th edition (DSM-IV). We examined incident and recurrent depression in participants without or with a history of major depression, respectively. We genotyped 5 single-nucleotide polymorphisms (SNPs) spanning CYP11B1. We used multivariable analyses to adjust for age, body mass index, cardiovascular ischemic pathologies, hypertension, cognitive impairment and anxiety. RESULTS: In women, rs6471580 and rs7016924 were associated with a 50% lower rate of incident (new-onset) late-life depression, and rs11783855 was associated with a 2.4-fold higher rate of late-life depression. These associations remained after correction for multiple testing, but we found no associations for recurrent depression in women or men. LIMITATIONS: This study focused on the major gene involved in corticosteroid biosynthesis, but other genes may also be implicated in this pathway. CONCLUSION: Variants of the CYP11B1 gene appear to be susceptibility factors for late-life depression in a sex-specific manner.